PENGARUH MOTIVASI EKSTRINSIK, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL INTERVENING - Sulistyowati, Nofi; Akhmadi, Akhmadi; Lutfi, Lutfi (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2017)
Aims of this studi is to measure the relationship of Extrinsic Motivation, Physical Work Environment, Employee Job Satisfaction (as intervening variable) and Employee Performance. Structural Equation Modeling (SEM) analysis was used with tools or software SmartPLS. Structural Equation Modeling (SEM) analysis was used with tools or software using SmartPLS. Based on the results of the mediation effect that the VAF value of 0.854 is categorized as full mediation and the effect is positive, its means that Extrinsic Motivation had influence on Employee Performance throught Job Satisfaction. The results showed that Extrinsic Motivation has not been able to improve Employee Performance directly, but if Extrinsic Motivation of employees increased and able to influence Employee Satisfaction then indirectly improve Employee Performance. On the other hand, the results of the mediation calculation showed that the Physical Work Environment has not been able to improve Employee Performance directly, but if the Physical Work Environment increases and is able to influence Job Satisfaction Employee then indirectly improve Employee Performance. Its means that the improvement of Employee Performance must be through Job Satisfaction first. Theoretically, this model is a full mediation, where the relationship between Physical Work Environment directly to Employee Performance has no effect, but the relationship between Physical Work Environment to Job Satisfaction and from Job Satisfaction to Employee Performance is significant.